2004
DOI: 10.1111/j.1468-2982.2004.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sumatriptan on Capsaicin-Induced Carotid Haemodynamic Changes and CGRP Release in Anaesthetized Pigs

Abstract: It is suggested that during a migraine attack capsaicin-sensitive trigeminal sensory nerves release calcitonin gene related peptide (CGRP), resulting in cranial vasodilatation and central nociception. Hence, inhibition of trigeminal CGRP release may prevent the above vasodilatation and, accordingly, abort migraine headache. Therefore, this study investigated the effects of sumatriptan (100 and 300 microg/kg, i.v.) on capsaicin-induced carotid haemodynamic changes and on CGRP release. Intracarotid (i.c.) infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…For this purpose, a 0.5 mm (external diameter) needle, connected to a suitable catheter, was inserted into the right common carotid artery for the continuous infusion of phenylephrine by another motor‐driven syringe. This phenylephrine‐induced carotid vasoconstriction, which allowed us to obtain greater vasodilator responses (Arulmani et al ., 2004a), was compared with the effects produced after 10‐min i.v. infusions of the highest doses of sumatriptan, donitriptan, PNU‐142633, PNU‐109291 or equivalent volumes of physiological saline.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…For this purpose, a 0.5 mm (external diameter) needle, connected to a suitable catheter, was inserted into the right common carotid artery for the continuous infusion of phenylephrine by another motor‐driven syringe. This phenylephrine‐induced carotid vasoconstriction, which allowed us to obtain greater vasodilator responses (Arulmani et al ., 2004a), was compared with the effects produced after 10‐min i.v. infusions of the highest doses of sumatriptan, donitriptan, PNU‐142633, PNU‐109291 or equivalent volumes of physiological saline.…”
Section: Methodssupporting
confidence: 88%
“…The release of endogenous CGRP can be experimentally induced by either trigeminal electrical stimulation (Buzzi et al ., 1991; Goadsby and Edvinsson, 1993) or chemical stimulation with capsaicin (Potenza et al ., 1994; Hou et al ., 2002; Dux et al ., 2003). Interestingly, the water‐soluble antimigraine drug, sumatriptan (see Humphrey et al ., 1991), attenuated the increased release of CGRP evoked by trigeminal electrical stimulation in rats and cats (Buzzi et al ., 1991; Goadsby and Edvinsson, 1993), but failed to modify the carotid vasodilatation and the increased release of CGRP induced by capsaicin in pigs (Arulmani et al ., 2004a). In this context, it is noteworthy that sumatriptan does not easily cross an intact blood–brain barrier (see Humphrey et al ., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Summ et al 24 found that a TRPV1 antagonist did not affect responding to mechanically induced cortical spreading depression or to electrical stimulation of the middle meningeal artery/dura mater, although it did affect response to capsaicin stimulation. Arulmani et al 25 found that sumatriptan did not inhibit CGRP release from intracarotid capsaicin injections and concluded that sumatriptan's main effect must then be to promote cranial vasoconstriction. Yan et al 26 found that acid‐sensitive currents in dural neurons were not modulated by capsazepine, a TRPV1 antagonist, but were strongly affected by amiloride, an acid‐sensing ion channel antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of CGRP in the pathophysiology of migraine is further strengthened by the observation that olcegepant (BIBN4096BS, Doods et al 2000), a CGRP receptor antagonist, is effective in the acute treatment of migraine attacks (Olesen et al 2004). Capsaicin has been widely used in various in vivo models of migraine to induce cranial vasodilatation, which is attributed to endogenous release of neuropeptides, especially CGRP (Akerman et al 2003; Arulmani et al 2004a; Gupta et al 2006a). The involvement of CGRP is further substantiated in all these in vivo studies by the fact that the capsaicin-induced vascular responses are all amenable to blockade with CGRP receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%